Efeito anti-asmático do metalodoador de óxido nítrico(FOR811A) em camundongos swiss - Costa, Paula Priscila Correia (2018)
Allergic asthma is characterized by chronic inflammation of the airways, which triggers recurrent bronchial hyperreactivity due to the imbalance between bronchoconstriction and bronchodilation. Increasing evidence points to an important role of nitric oxide (NO) in pulmonary physiology, as well as in pathological conditions. Therefore, NO donors, such as ruthenium nitrosyl compounds, emerge as important pharmacological tools. Studies in bronchiolar and tracheal smooth muscle have shown that the main target of NO is the soluble guanylate cyclase enzyme (GCs). When activated, it increases cGMP levels. In this context, the objective of this work was to evaluate the effects of a complex nitrosyl ruthenium cis- [Ru (bpy) 2 (2-MIM) (NO)] 3+ (FOR811A) complex in murine model of allergic asthma. The project was approved by the Ethics Committee on the use of animals CEUA / UECE under protocol number 2068307/2018. To do so, in vivo studies were performed in which female swiss mice (25 g, 6 weeks old) were sensitized (3 ip injections of 100 μg ovalbumin on days 0, 7 and 14) and submitted to challenges with inhalations with ovalbumin (10mg / mL for 20 minutes, on days 26, 27 and 28) and further in silico (molecular docking) studies to evaluate protein drug interactions.Experimental groups were divided into control animals in the presence (SM) or absence (SS) of the FOR811A and animals sensitized with ovalbumin in presence (OM) or absence of FOR811A (OS). Animals of the control groups (SS and SM) received saline solution (NaCl 0.9%) in a protocol identical to that described above. On day 29, animals from the groups (SM and OM) received gavage (0,2mL) of FOR811A (0.75mg / kg) and the other groups (SS and OS) received gavage (0.2mL) of saline ( 0,9%), single dose. On day 30, all groups were anesthetized with Ketamine (10mg / kg, ip) and Xilazine (2mg / kg, ip) for pulmonary mechanics experiments and then lung collection for oxidative damage analyzes (nitrite / nitrate and GSH), inflammatory lesion (myeloperoxidase, Il-1β and Il-4) and histology. Thus, in lung mechanics, the FOR811A promoted a decrease in the parameters of pressure-volume curve (PV), hysteresis (n), tissue elastance (H) and tissue resistance (G) and area pathways (Rn), as well as values of static compliance (Cst) and inspiratory capacity (CI) to that of the control group (SS). In the molecular docking the FOR811A demonstrated strong binding to the distal portion of the Heme group evidencing the residue (Cys 141). However, FOR811A did not decrease oxidative damage, remodeling and inflammatory damage caused by asthma, but decreased IL-4 levels (Th2 response) and did not alter IL-1β levels (Th1 response). Therefore, the action of the studied ruthenium compound, FOR811A, demonstrated a protective effect on asthma through its potential for smooth muscle relaxation and a decrease in the allergic condition, possibly due to its action on GCs through the distal portion of the Heme group evidencing the residue (Cys 141) cysteine portion, suggested by molecular docking.